(untitled) (Conferencea, 2022)
This article represents that degreenymy as a stylistic phenomenon in comparison with other expressive facts of language and speech, despite the fact that gradation is presented in the vast majority of textbooks and dictionaries on stylistics, speech culture, and rhetoric. A comprehensive description of gradation as an expressive phenomenon of the modern English and Uzbek literary discourse